COVID-19 vaccination acceptance among older adults: A qualitative study in New South Wales, Australia - Bianca Bullivant; Katarzyna T. Bolsewicz; Catherine King; Maryke S. Steffens (Elsevier, 2023)
Objectives: The COVID-19 pandemic has had a severe impact on people across the world, particularly older adults who have a higher risk of death and health complications. We aimed to explore older adults' intention towards COVID-19 vaccination and factors that influenced their motivation to get vaccinated. Study design: A qualitative study was conducted in New South Wales, Australia (April 2021), involving interviews with older adults (aged 70 years and older). Methods: In-depth interviews were carried out with 14 older adults on their perceptions around COVID-19 vaccination. The COVID-19 vaccination program had just commenced at the time of data collection. We thematically analysed interviews and organised the themes within the Behavioural and Social Drivers of Vaccination (BeSD) Framework. Results: We found that most participants were accepting of COVID-19 vaccination. Participants' motivation to get vaccinated was influenced by the way they thought and felt about COVID-19 disease and vaccination (including perceptions of vaccine safety, effectiveness, benefits, COVID-19 disease risk, and vaccine brand preferences) and social influences (including healthcare provider recommendation, and influential others). The uptake of COVID-19 vaccination was also mediated by practical issues such as access and affordability. Conclusions: Efforts to increase COVID-19 vaccination acceptance in this population should focus on highlighting the benefits of vaccination. Support should be given to immunisation providers to enhance efforts to discuss and recommend vaccination to this high-risk group.